A Florentine Tragedy; La Sainte Courtisane - Wilde, Oscar, 1854-1900; Ross, Robert Baldwin, 1869-1918 (Salt Lake City, UT : Project Gutenberg, 1998)
"A Florentine Tragedy; La Sainte Courtisane" by Oscar Wilde is a collection of dramatic works likely composed during the late 19th century. This book contains two plays: "A Florentine Tragedy," which reflects themes of desire, betrayal, and fatalism, and "La Sainte Courtisane," which explores concepts of love and repentance. Both pieces are richly poetic and reflect Wilde's signature wit and artistic sensibilities. In "A Florentine Tragedy," the narrative revolves around Simone, a merchant, and his wife Bianca, who becomes the object of desire for a nobleman, Guido Bardi. The tension escalates into a violent confrontation when Simone discovers Guido's intentions toward Bianca. The play explores themes of possession, honor, and the despair that comes with unbridled passion. In contrast, "La Sainte Courtisane" is a fragmented work that recounts the encounter between Myrrhina, a courtesan, and a young hermit named Honorius, highlighting a struggle between earthly beauty and spiritual desire. The dialogues are laden with allegorical significance and evoke the complexities of human emotions and the search for redemption. (This is an automatically generated summary.)
A Florentine tragedy: a fragment -- La sainte courtisane: a fragment.
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Florentine_Tragedy
Release date is 1998-05-01
Transcribed from the 1917 Methuen and Co. edition of Salomé etc. by David Price
Keywords: Drama